CLASSIFICATION OF WORKS ON ISLAMIC LAW WRITTEN IN MAVERANNAHR DURING THE MEDIEVAL (Academia Science Repository, 2023)
It is known from history that Movarounnahr is a land where various sciences developed and many scientists grew up. The sciences of Islam, especially tafsir, hadith, fiqh and Sufism, developed in this region at different periods. Among these disciplines, Islamic law went through two periods: the formative and classical periods during the X-XII centuries. During these centuries, many scholars wrote rare works on a range of issues related to the field of Islamic law. This article reveals the specific aspects of several works on Islamic law written in the X-XII centuries.